2016
DOI: 10.1371/journal.pone.0163646
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Lipid Modification Is Required for the Stable Accumulation of CyanoQ in Synechocystis sp. PCC 6803

Abstract: The CyanoQ protein has been demonstrated to be a component of cyanobacterial Photosystem II (PS II), but there exist a number of outstanding questions concerning its physical association with the complex. CyanoQ is a lipoprotein; upon cleavage of its transit peptide by Signal Peptidase II, which targets delivery of the mature protein to the thylakoid lumenal space, the N-terminal cysteinyl residue is lipid-modified. This modification appears to tether this otherwise soluble component to the thylakoid membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The role of the lipid moiety in the function of Psb27, CyanoP, CyanoQ, and Ycf48 is not clear, although Juneau et al have concluded that lipidation may stabilize the CyanoQ protein [ 25 ]. Since PSII biogenesis seems to occur in specific regions of the thylakoid membranes, lipids may help maintain the location of assembly factors within these regions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the lipid moiety in the function of Psb27, CyanoP, CyanoQ, and Ycf48 is not clear, although Juneau et al have concluded that lipidation may stabilize the CyanoQ protein [ 25 ]. Since PSII biogenesis seems to occur in specific regions of the thylakoid membranes, lipids may help maintain the location of assembly factors within these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins might be tethered to the membrane just to limit diffusion in a two-dimensional space, which can be also mediated by a transmembrane helix (e.g. evolved from a former signal peptide) or the lipid moiety might play an additional role in the localization of the protein in a specific membrane or part of a membrane (Ferguson 1991;Okuda and Tokuda 2011;Juneau et al 2016). For photosynthesis associated CyanoQ, the lipidation is essential for processing and accumulation of the protein in the thylakoids, independent of the signal peptide itself, which emphasizes the importance of the process (Juneau et al 2016).…”
Section: Discussionmentioning
confidence: 99%